IMPLEMENTASI KEBIJAKAN RETRIBUSI JASA UMUM DALAM MENUNJANG PENDAPATAN ASLI DAERAH KOTA PALU - Rahman, Arif (Katalogis, 2015)
The problem in this study was the implementation of general service retribution policy in supporting the local original income of Palu City. The purpose of this study was to determine the implementation of general service retribution policy in supporting the local original income of Palu City. The data used in this study were primary and secondary data. The data collection was done by using literature study and field research. The determination of informants in this study was purposive sampling technique with informants amounting to seven (7) people. Data analysis technique used in this study was descriptive qualitative data analysis with the approach of Miles and Huberman model, namely data reduction, data presentation, conclusion/verification. The theory used in this study was the theory of George Edward III. The results show that the implementation of general service retribution policy in supporting the local original income of Palu City had not run optimally, based on the four indicators which were used as analytical tools. Communication which was not optimal, for the transformation had not been effective in some relevant technical agencies, the unclear information led to miscommunication among institutions and society, the consistence in providing information through dissemination to the public was still less done. Resources which were not optimal, for the lack of human resources quality, the ownership of operational funds still needed attention, the facilities and infrastructures were still limited, and the information resources were received relating to the knowledge of what to do were not shared by all existing staff. Bureaucracy Structure which was not optimal, for the bureaucratic structures and mechanisms were not going well: there was no standard operating procedure (SOP), the institutional structure of the organization was not representative, and there were overlapping authorities in duties and functions. While only one indicator which went well: Disposition, for the behaviors and attitudes of implementers in accepting any command had been going well, the effect of disposition build honesty to the staff in stages, the spread of responsibility were quite good, no staff problems in the bureaucracy associated with the provision of workloads, the provision of incentives to build motivation, and the morale had already been done.